The Influence of Financial Literacy Aspects in Supporting Marketing Patterns of MSMEs in Parepare City with Financial Technology as a Moderating Variable - Wijaya, Ilham; Naninsih , Nur; Kurniawaty, Kurniawaty (Economos : Jurnal Ekonomi dan Bisnis, 2024)
This study aims to determine: (1) the influence of financial knowledge, attitude, behavior, and the utilization of financial technology on the marketing patterns of MSMEs in Parepare City, and (2) the impact of financial knowledge, attitude, and behavior on the marketing patterns of MSMEs in Parepare City when moderated by the utilization of financial technology. The research was conducted on MSME development in Soreang District, Parepare City, from July to August 2023. The research employs observation methods, distribution of questionnaires, and literature studies, with a sample of 98 MSMEs determined using the Slovin formula at a 10% error margin. Data were analyzed using the Partial Least Square (PLS) data analysis method and inferential statistical analysis. The findings reveal that financial knowledge and financial technology have a positive but not significant impact on the application of marketing patterns by MSME actors in Parepare City. Financial attitude and behavior have a positive and significant influence on the application of marketing patterns by MSME actors in Parepare City. Financial knowledge demonstrates a positive and significant effect on the application of marketing patterns by MSME actors in Parepare City after being strengthened by the utilization of financial technology. Financial attitude and behavior have a positive but not significant impact on the application of marketing patterns by MSME actors in Parepare City, even when mediated by the utilization of financial technology.